Respuesta :
Step-by-step explanation:
[tex]\displaystyle \lim_{x \to 0} \left(\dfrac{\sqrt{x^2 + 3x + 1} - 1}{\arcsin 2x} \right)[/tex]
Note that as [tex]x \rightarrow 0[/tex], the ratio becomes undefined. Using L'Hopital's Rule, where
[tex]\displaystyle \lim_{x \to c} \dfrac{f(x)}{g(x)} = \lim_{x \to c} \dfrac{f'(x)}{g'(x)} [/tex]
where f'(x) and g'(x) are the derivatives of the functions f(x) and g(x), respectively. Note that
[tex]f(x) = \sqrt{x^2 + 3x + 1} \:\:\text{and}\:\: g(x) = \arcsin 2x[/tex]
[tex]f'(x) = \dfrac{2x + 3}{2(\sqrt{x^2 + 3x + 1})}[/tex]
[tex]g'(x) = \dfrac{2}{\sqrt{1 - 4x^2}}[/tex]
Therefore,
[tex]\displaystyle \lim_{x \to 0} \dfrac{f'(x)}{g'(x)} = \lim_{x \to 0} \dfrac{2x + 3}{2(\sqrt{x^2 + 3x + 1})} \times \left(\dfrac{\sqrt{1 - 4x^2}}{2} \right)[/tex]
or
[tex]\displaystyle \lim_{x \to 0} \left(\dfrac{\sqrt{x^2 + 3x + 1} - 1}{\arcsin 2x} \right) = \dfrac{3}{4}[/tex]